Re-imaginations of women"s theology for female bodies: A panacea for a future with hope among teen girls selling sex at Epworth Booster, Harare - Mujinga, Martin (HTS teologiese studies, 2022)
The perpetual decline of Zimbabwe’s socio-economic situation can be found in the country legalising prostitution, which it used to regard as an act of criminality. This legalisation promoted the trade from being an offense to a lifestyle and from being an act of immorality to a profession. Prostitutes were also advanced from being social outcasts to commercial sex workers. Although the law appeared to financially empower prostitutes, its negative impact is seen in the level it dehumanises teen girls as they turn themselves into sex objects. Cases of school dropouts among teen girls and human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) are some of the evidences of the negative impact of prostitution, caused by their belief that ‘unprotected sex pays more’. The location of the study was Epworth Booster in Harare, Zimbabwe. Using an African feminist theology framework, this article aims to analyse how women’s theology can be used as a panacea to restore dignity and hunhu-ism to the teen girls whose bodies have been exposed to abuse by their purported fathers. The article uses both unstructured and focus group interviews to collect data from three health personnel and 10 teen girls, respectively. The article grapples with the fact that the legalisation of prostitution in Zimbabwe seriously affected both the social and religious life of teen girls as they risk their lives in order to earn a living, and African feminist theology should be applied to defend these vulnerable girls.Contribution: In the context of socio-economic depletion and laws that suppress women in the name of empowering them, rereading and application of women’s theology should protect women and offer them a future with hope.